2014
DOI: 10.1039/c3cs60463b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer across molecular bridges: electron- and hole-transfer superexchange pathways

Abstract: Photoinduced electron transfer plays key roles in many areas of chemistry. Superexchange is an effective model to rationalize photoinduced electron transfer, particularly when molecular bridges between donor and acceptor subunits are present. In this tutorial review we discuss, within a superexchange framework, the complex role played by the bridge, with an emphasis on differences between thermal and photoinduced electron transfer, oxidative and reductive photoinduced processes, charge separation and charge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
168
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 67 publications
3
168
1
1
Order By: Relevance
“…[52] However, the addition of tetra-n-hexylammonium chloride (THACl) as an anion source to a solution of TTF-C4P and Li + @C 60 in PhCN induced electron transfer from TTF-C4P to Li + @C 60 by binding of Cl À to the calix [4]pyrrole moiety to produce the radical ion pair complex Li…”
Section: Electron-transfer Properties Of LImentioning
confidence: 99%
See 2 more Smart Citations
“…[52] However, the addition of tetra-n-hexylammonium chloride (THACl) as an anion source to a solution of TTF-C4P and Li + @C 60 in PhCN induced electron transfer from TTF-C4P to Li + @C 60 by binding of Cl À to the calix [4]pyrrole moiety to produce the radical ion pair complex Li…”
Section: Electron-transfer Properties Of LImentioning
confidence: 99%
“…[53] Such enhanced electron-acceptor ability of Li + @C 60 has made it possible to achieve more efficient thermal and photoinduced electron-transfer reduction of Li + @C 60 than that of C 60 , as discussed below. Li + @C 60 has been reported to form a supramolecular complex with tetrathiafulvalene calix [4]pyrrole (TTF-C4P). [52,54,55] TTF-C4P has electron-rich TTF moieties and its structure is changed by the addition of an anion from the 1,3-alternate conformation into the cone conformation, which can include pristine C 60 .…”
Section: Electron-transfer Properties Of LImentioning
confidence: 99%
See 1 more Smart Citation
“…[4,[13][14][15] One general strategy to extend the lifetime of these CS states is to lengthen the bridge or linker between the ruthenium core and the peripheral electron-donating/accepting moieties thereby decreasing the rate of back electron transfer. [16][17][18][19][20] Ruthenium based dyads and triads have been investigated with both saturated and π-conjugated linkers between the core and the peripheral substituents, in an effort to mediate electron transfer. [4,[21][22][23] As expected, it has been shown that both the length and the nature of the linker greatly influence the properties of molecular wire-like electron and energy transfer behavior within these assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of FLI, a versatile fluorescence off/on approach, named photoinduced electron transfer (PET), is widely used for the fluorogenic probe design [13]. In general, PET refers to an excited state electron transfer process by which excited electron is transferred from the donor to acceptor [14]. Recently, many PETbased fluorescent probes were designed and utilized to detect the quantity of biomacromolecules, such as GPCRs, ion channels, DNAs, and RNAs [15].…”
mentioning
confidence: 99%